2013
DOI: 10.1155/2013/365830
|View full text |Cite
|
Sign up to set email alerts
|

Gastric ESD under Heparin Replacement at High-Risk Patients of Thromboembolism Is Technically Feasible but Has a High Risk of Delayed Bleeding: Osaka University ESD Study Group

Abstract: Objectives. Heparin replacement (HR) is often performed in patients with a high risk of thrombosis undergoing endoscopic procedures. However, information about the influence of HR is scarce. The aim of this study is to assess the clinical impact of HR for gastric endoscopic submucosal dissection (ESD). Methods. This is a retrospective study comprising approximately 1310 consecutive gastric neoplasms in 1250 patients, who underwent ESD in 5 institutes. We assessed the clinical findings and outcomes of ESD unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
88
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 18 publications
4
88
0
1
Order By: Relevance
“…Moreover, bleeding has been associated with high bleeding risk procedures and taking warfarin with heparin bridging [29, 30]. Furuhata et al [31] and Yoshio et al [22] also reported that heparin alternative therapy significantly increases the risk of post-ESD bleeding for EGC [22, 31]. Our data also showed that bleeding after gastric ESD occurred in 14% of patients taking warfarin with heparin bridging.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, bleeding has been associated with high bleeding risk procedures and taking warfarin with heparin bridging [29, 30]. Furuhata et al [31] and Yoshio et al [22] also reported that heparin alternative therapy significantly increases the risk of post-ESD bleeding for EGC [22, 31]. Our data also showed that bleeding after gastric ESD occurred in 14% of patients taking warfarin with heparin bridging.…”
Section: Discussionsupporting
confidence: 64%
“…12 Heparin replacement was not identified as a significant risk factor in 1 study, 43 although an opposite result was found in another study. 40 Gastroprotective agents were associated with lower PPB in patients undergoing AT in 1 study. 54 Corticosteroid use was not identified as a risk factor for PPB.…”
Section: Risk Factors For Ppbmentioning
confidence: 89%
“…Age was not identified as a risk factor in most studies, with only 1 study reporting that younger patients may be at higher risk for PPB. 34 Furthermore, 10 studies found no significant differences in elderly patients, 19,25,30,[35][36][37][38][39][40][41] although 1 study identified age > 80 years as an independent risk factor for PPB. 42 PPB rates were similar between genders in most studies, [13][14][15][16][17][18][20][21][22][23][25][26][27][28][29][30][31][32][33][34]36,39,[42][43][44] with only 1 study reporting an association male sex associated with PPB.…”
Section: Risk Factors For Ppbmentioning
confidence: 99%
“…A recent study showed that the ratio of bleeding after ESD was higher in the anticoagulant agents group than in the nonanticoagulants agent group, 23.3% and 2%, respectively; however, the study did not examine the methods of drug use or which antithrombotic drugs may increase the rate of bleeding (27). In another study, the use of heparin caused a higher risk of delayed bleeding after gastric ESD (33). Takeuchi found that combining LDA with warfarin and longer ESD operations increased the rate of post-ESD bleeding (27).…”
Section: Discussionmentioning
confidence: 97%